Discordant emotions: The affective dynamics of anti-LGBT campaigns in Indonesia - Thajib, Teuku Ferdiansyah (Indonesia and the Malay World, 2022)
This study focuses on disaggregating the affective dynamics that constitute the growing anti-LGBT campaigns in Indonesia. My analysis draws on the virtual and physical public discourse which has been hosting overt animosity towards sexual and gender minorities in Indonesia from 2016 to 2018. This article opens with a historical overview of the climate of hostility which characterised sexual and gender politics in Indonesia leading to the current ‘eruption’ of the anti-LGBT campaign in Indonesia in 2016. Then I focus on several case studies to shed light on how the violent delegitimisation of sexual and gender minorities in the country involves affective shifts from shame and fear to care and protection. At the outset, narratives that combine shame and fear have been instrumentalised by elites and non-elites in the country to galvanise volatile reactions within society members. In the course of time, the use of inflammatory language based on shame and fear is gradually displaced by scripts of care and protection. This situation signals how even though anti-LGBT campaigns in Indonesia have seemingly adopted a more benevolent outlook, they are fundamentally geared towards similarly violent aims.<br
Keywords: anti LGBT Campaign; care and protection; shame and fear